SARS-CoV-2 Infection Induces Ferroptosis of Sinoatrial Node Pacemaker Cells. Issue 7 (8th March 2022) - Han, Yuling; Zhu, Jiajun; Yang, Liuliu; Nilsson-Payant, Benjamin E.; Hurtado, Romulo; Lacko, Lauretta A.; Sun, Xiaolu; Gade, Aravind R.; Higgins, Christina A.; Sisso, Whitney J.; Dong, Xue; Wang, Maple; et al.
Abstract : Background: Increasing evidence suggests that cardiac arrhythmias are frequent clinical features of coronavirus disease 2019 (COVID-19). Sinus node damage may lead to bradycardia. However, it is challenging to explore human sinoatrial node (SAN) pathophysiology due to difficulty in isolating and culturing human SAN cells. Embryonic stem cells (ESCs) can be a source to derive human SAN-like pacemaker cells for disease modeling. Methods: We used both a hamster model and human ESC (hESC)–derived SAN-like pacemaker cells to explore the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on the pacemaker cells of the heart. In the hamster model, quantitative real-time polymerase chain reaction and immunostaining were used to detect viral RNA and protein, respectively. We then created a dual knock-in SHOX2:GFP;MYH6:mCherry hESC reporter line to establish a highly efficient strategy to derive functional human SAN-like pacemaker cells, which was further characterized by single-cell RNA sequencing. Following exposure to SARS-CoV-2, quantitative real-time polymerase chain reaction, immunostaining, and RNA sequencing were used to confirm infection and determine the host response of hESC-SAN–like pacemaker cells. Finally, a high content chemical screen was performed to identify drugs that can inhibit SARS-CoV-2 infection, and block SARS-CoV-2–induced ferroptosis. Results: Viral RNA and spike protein were detected in SAN cells in the hearts of infected hamsters. We established an efficient strategy to derive from hESCs functional human SAN-like pacemaker cells, which express pacemaker markers and display SAN-like action potentials. Furthermore, SARS-CoV-2 infection causes dysfunction of human SAN-like pacemaker cells and induces ferroptosis. Two drug candidates, deferoxamine and imatinib, were identified from the high content screen, able to block SARS-CoV-2 infection and infection-associated ferroptosis. Conclusions: Using a hamster model, we showed that primary pacemaker cells in the heart can be infected by SARS-CoV-2. Infection of hESC-derived functional SAN-like pacemaker cells demonstrates ferroptosis as a potential mechanism for causing cardiac arrhythmias in patients with COVID-19. Finally, we identified candidate drugs that can protect the SAN cells from SARS-CoV-2 infection.